Traditional Herbal Medicine in Mesoamerica: Toward Its Evidence Base for Improving Universal Health Coverage - Geck, Matthias S.; Cristians, Sol; Berger-González, Mónica; Casu, Laura; Heinrich, Michael; Leonti, Marco (Frontiers in Pharmacology, 2020)
The quality of health care in Mesoamerica is influenced by its rich cultural diversity and characterized by social inequalities. Especially indigenous and rural communities confront diverse barriers to accessing formal health services, leading to often conflicting plurimedical systems. Fostering integrative medicine is a fundamental pillar for achieving universal health coverage (UHC) for marginalized populations. Recent developments towards health sovereignty in the region are concerned with assessing the role of traditional medicines, and particularly herbal medicines, to foster accessible and culturally pertinent healthcare provision models. In Mesoamerica, as in most regions of the world, a wealth of information on traditional and complementary medicine has been recorded. Yet these data are often scattered, making it difficult for policy makers to regulate and integrate traditionally used botanical products into primary health care. This critical review is based on a quantitative analysis of 28 survey papers focusing on the traditional use of botanical drugs in Mesoamerica used for the compilation of the ‘Mesoamerican Medicinal Plant Database’ (MAMPDB), which includes a total of 12,537 use-records for 2188 plant taxa. Our approach presents a fundamental step towards UHC by presenting a pharmacological and toxicological review of the cross-culturally salient plant taxa and associated botanical drugs used in traditional medicine in Mesoamerica. Especially for native herbal drugs, data about safety and effectiveness are limited. Commonly used cross-culturally salient botanical drugs, which are considered safe but for which data on effectiveness is lacking constitute ideal candidates for treatment outcome studies.